The contribution of alternative polyadenylation to the cancer phenotype - Masamha, Chioniso P; Wagner, Eric J (Carcinogenesis (New York), 2018)
There is experimental evidence to suggest that tandem untranslated region APA plays a major role in the expression of oncogenes during oncogenesis. In addition, there are other potential ramifications of APA on other cellular mRNAs whose role in cancer is still being deciphered. Abstract Eukaryotic 3′-end formation is a critical step for mRNA maturation and involves a requisite cleavage and polyadenylation event downstream of a polyadenylation signal. Recent discoveries suggest that in nearly 70% of human genes, cleavage and polyadenylation can occur at multiple locations through a process known as alternative polyadenylation (APA). Therefore, APA is a form of co-transcriptional gene regulation that has the potential to greatly expand mRNA transcript diversity. There are two general types of APA. The first includes alternative splicing events (splicing-APA) that result in changes to the coding sequence, and the second does not involve alternative splicing (tandem untranslated region-APA). The latter form of APA occurs within the same terminal exon, thereby only changing the 3′-untranslated region length and content. The role of APA in transformation and cancer is still being deciphered and has been the subject of intensive investigation by multiple groups. Here, we provide a general summary of APA and how it can differentially impact mRNA stability, translation and localization in cis. In addition, we discuss more indirect implications of APA on mRNA transcripts. The latter is based upon the concept that APA can induce the reorganization of both microRNA-mRNA and RNA-binding protein-mRNA interactions. We use these general models as a platform to describe what is known about how tumors manipulate the APA of oncogenes to further drive tumorigenesis. Finally, we briefly discuss the role that next-generation sequencing has played in identifying APA regulators and key transcripts that alter 3′-untranslated region length in cancer.